Development of an Indoor Positioning System for Smart Aging Applications - Ganesh, Guha (My University, 2022)
The development of an Indoor Positioning System that requires a non-invasive setup and installation process is outlined in this dissertation. The Hardware, Mechanical and Software components are described in complete detail. The system operates using a hybrid of Bluetooth Low Energy (BLE) signal strength analysis and proximity sensor data collection to determine the location of a known Bluetooth compatible device. Additionally, a dynamic remote calibration protocol was developed to ensure a safe and smooth setup and integration process in any location the system is implemented. The system uses custom designed beacon modules that connect directly to outlets in designated rooms. These beacons relay sensor and BLE data to a Hub module that collects and stores all this data locally and on a cloud server. These features ensured that the IPS is a completely remote device that can be setup independently by the user. To our knowledge, this is the only Indoor Positioning System that does not require prior knowledge of the location of integration and the need for an in-person setup and calibration process. Additionally, despite the lack of an extensive setup and calibration process the system still operates at an accurate room detection percentage of 98%. To further prove its ease of use the system has been implemented in a clinical study where several older adults (65+) have integrated this system within their homes. This system has been designed to act as the foundation for larger scale healthcare monitoring applications.
Keywords: Smart Home, Indoor Positioning, Aging in Place